2021
DOI: 10.1002/jsfa.11263
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen leaching and grey water footprint affected by nitrogen fertilization rate in maize production: a case study of Southwest China

Abstract: BACKGROUND: Effective nitrogen (N) management measures are required to control environmental problems caused by N fertilizer use in intensive maize production systems. Soil N losses associated with high precipitation and over-fertilization in maize production can cause substantial environmental problems, whereas there is a lack of quantitative data and effective study countermeasures. A 2-year field study was conducted in the subtropical maize production system in Southwest China to quantify N leaching under v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(57 reference statements)
2
2
0
Order By: Relevance
“…Similarly, Anjum et al (2018) also reported the highest mean grain yield (4,100 kg ha −1 ) of maize at 180 N kg ha −1 applied in three split applications: 60 kg ha −1 before sowing, 60 kg ha −1 at vegetative stages, and 60 kg ha −1 at the tassel initiation stage. Consistent with this result, Yao et al (2021) reported that high rain during the pretasseling and postsilking stages of maize led to a high rate of N leaching and lower N uptake, which resulted in lower grain yields. Similarly, Jabloun et al (2015) also pointed out that excess water can cause root damage or restrict root development, which affects the absorption of water and nutrients by plants and causes N deficiency by leaching.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similarly, Anjum et al (2018) also reported the highest mean grain yield (4,100 kg ha −1 ) of maize at 180 N kg ha −1 applied in three split applications: 60 kg ha −1 before sowing, 60 kg ha −1 at vegetative stages, and 60 kg ha −1 at the tassel initiation stage. Consistent with this result, Yao et al (2021) reported that high rain during the pretasseling and postsilking stages of maize led to a high rate of N leaching and lower N uptake, which resulted in lower grain yields. Similarly, Jabloun et al (2015) also pointed out that excess water can cause root damage or restrict root development, which affects the absorption of water and nutrients by plants and causes N deficiency by leaching.…”
Section: Discussionsupporting
confidence: 70%
“…Consistent with this result, Yao et al. (2021) reported that high rain during the pretasseling and postsilking stages of maize led to a high rate of N leaching and lower N uptake, which resulted in lower grain yields. Similarly, Jabloun et al.…”
Section: Discussionsupporting
confidence: 55%
“…This trend might be explained by areas with greater precipitation being associated with more weathered, infertile soils. In environments with heavy rainfall, the loss of nutrients from surface runoff and leaching often serve as a major limitation to soil health (Yao et al., 2021). It has been shown that Phaseolus accessions with longer, denser root hairs have enhanced phosphorus acquisition in phosphorus deficient soil, and many of the species displaying long root hair phenotypes are endemic to regions with soils that are volcanic in origin with inherently low phosphorus availability (Singh Gahoonia & Nielsen, 2004; Lynch, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Over-fertilization results in a low N use efficiency and low economic benefits. It also exacerbates nitrogen leaching and volatilization, and causes a range of environmental problems, such as soil acidification and the eutrophication of water bodies [4,5]. Meanwhile, corresponding shifts in soil microbial properties have been widely reported, including the depletion of soil microbial biomass, alterations in species composition, and decreases in diversity [6,7].…”
Section: Introductionmentioning
confidence: 99%